Exploring the adoption of technology assisted services in the health care industry - Topaçan, Ümit. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
With the rapid development of medical technologies, medical industry benefit from various new emergent tools in order to increase quality and lower health expenditures in their services. Telemedicine is one of the recent inventions in the industry. It brings distant and dispersed patients together with their medical providers by means of telecommunication technologies. Users of medical electronic services, including health care providers and patients, cannot benefit from them in a full capacity unless using them comfortably. The aim of this study is to evaluate determinants of health information service adoption and to assess desirability of an electronic health service prototype. This study started with a literature survey in order to construct the theoretical background of the technology adoption. Then, two qualitative studies, namely interview and expert focus group; and one quantitative study, namely AHP, were conducted to expand the adoption taxonomy with participants’ creative ideas. After these studies experimental study, contains conjoint and regression analysis, was carried out. During conjoint analysis, service attributes that affect users’ preferences were explored. In addition, regression analysis results showed the determinants of users’ intention toward e-health information service usage. Electronic health information service researchers and designers can benefit from the results of this study.
Keywords: Telecommunication in medicine.; Medical telematics.; Public health -- Information services.